Struggle on their minds : the political thought of African American resistance - Zamalin, Alex, 1986- (Columbia University Press, 2017)
"The rise of the American economy, the persistence of social inequality, and the ongoing struggle for adequate political representation cannot be evaluated separately from slavery, the country's original sin. Five activists who have fought to incorporate slavery into American political discourse are the focus of this timely book, in which Alex Zamalin considers past African American resistance to underscore its future democratic necessity. He looks at the language and conceptions put forward by the American abolitionists David Walker and Frederick Douglass, the antilynching activist Ida B. Wells, the Black Panther Party organizer Huey P. Newton, and the prison reformer Angela Davis. Each through passionate argument revised the core values of the American political tradition and reformed ideas about power, justice, community, action, and the role of emotion in elective outcomes. Zamalin finds numerous examples in which political theory developed a more open and resilient conception of individual liberty after key moments of African American resistance provoked by these activists' work. Their thought encouraged slaves to revolt against their masters, black radical abolitionists to call for the eradication of slavery by any means necessary, black journalists to chastise American institutions for their indifference to lynching, and black radicals to police the police and to condemn racial injustice in the American prison system. Taken together, these movements pushed political theory forward, offering new language and concepts to sustain democracy in tense times. Struggle on Their Minds is a critical text for our contemporary moment, showing how constructive resistance can strengthen the practice of democracy and help disenfranchised groups achieve political parity."--Provided by publisher